Mercy Corps : sustainable innovation through corporate partnerships - Nagy, Andrea R.; Feinstein, Jonathan S., 1960- ([London] : SAGE, 2016)
Mercy Corps was known for its gutsy approach to disasters. While other relief and development organizations were scrambling to plan a response, Mercy Corps would already be on the ground with aid and skilled field workers. In addition to performing emergency relief, the agency had also developed strong programs in economic development using a 'community mobilization' approach that emphasized local control and sponsorship of projects. This case examines Mercy Corps' continued progression and development.
Originally Published in: Nagy, A. R., & Feinstein, J. (2008). Mercy Corps: Sustainable Innovation through Corporate Partnerships. 07-016. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Mercy Corps; Organizational change -- Case studies; Sustainable development -- Case studies; Technological innovations -- Case studies; Strategic alliances (Business) -- Case studies; Emergency management -- Case studies